Barrier films, packaging materials, and packaging bodies

JP2026165837APending Publication Date: 2026-10-14RM TOHCELLO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058443
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、酸素バリア性が向上したバリア性フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165837000001_ABST
    Figure 2026165837000001_ABST
Patent Text Reader

Abstract

To provide a barrier film with improved oxygen barrier properties. [Solution] The material comprises a polyethylene layer (101) containing an ethylene polymer and a barrier resin layer (102) containing a barrier resin. When a differential scanning calorimeter (DSC) is used to perform a first measurement where the temperature is raised from -50°C to 200°C at a heating rate of 10°C / min, and a second measurement where the temperature is held at 200°C for 5 minutes, then cooled from 200°C to -50°C at a cooling rate of 10°C / min, held at -50°C for 5 minutes, and then heated from -50°C to 200°C at a heating rate of 10°C / min, at least one endothermic peak is observed in the range of 100°C to 140°C and in the range of 150°C to 190°C in the second DSC curve 2, and the heat of fusion ΔH of the endothermic peak in the range of 0°C to 140°C in the DSC curve 1 is measured. 1st (J / g) and DSC curve 2, the heat of fusion ΔH for the endothermic peak between 0°C and 140°C. 2nd A barrier film (100) with a difference in (J / g) of 1.0 J / g or more and 50.0 J / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to barrier films, packaging materials, and packaging bodies. [Background technology]

[0002] Stretched polyethylene film is used, for example, as packaging film.

[0003] Patent Document 1 describes a polyethylene laminate for packaging materials comprising at least a stretched polyethylene film, an adhesive layer, and a heat-sealable polyethylene layer, wherein the adhesive layer contains a solvent-free adhesive. Furthermore, Patent Document 1 describes that it is possible to provide a polyethylene laminate for packaging materials that can significantly reduce the environmental burden while having high printability and strength.

[0004] Patent Document 2 describes a stretched polyethylene film made of a polyethylene-based resin composition containing polyethylene and petroleum resin, which is a uniaxially oriented or biaxially oriented film with a stretch ratio of 3 times or more. Furthermore, Patent Document 2 states that it is possible to provide a stretched polyethylene film that does not break even at high stretch ratios and has high strength. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2022-079510 [Patent Document 2] Japanese Patent Publication No. 2023-031061 [Overview of the project] [Problems that the invention aims to solve]

[0006] This invention provides a barrier film with improved oxygen barrier properties. [Means for solving the problem]

[0007] The inventors diligently studied to solve the above problems. As a result, in a film comprising a polyethylene layer and a barrier resin layer, in the DSC curve 2 (2nd Run) obtained by the second differential scanning calorimetry measurement using a differential scanning calorimetry (DSC), at least one endothermic peak was observed in each of the ranges of 100°C to 140°C and 150°C to 190°C, and the heat of fusion calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 1 (1st Run) obtained by the first differential scanning calorimetry measurement was ΔH 1st (J / g) is used, and the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 2 (2ndRun) obtained by the second differential scanning calorimetry, and is then given as ΔH. 2nd When (J / g), ΔH 1st -ΔH 2nd We found that setting the value within a predetermined range improves oxygen barrier properties.

[0008] In other words, the present invention provides the following barrier film, packaging material, and packaging body.

[0009] [1] It comprises a polyethylene layer and a barrier resin layer, The polyethylene layer contains an ethylene polymer. The barrier resin layer comprises a barrier resin. Using a differential scanning calorimeter (DSC), the process consists of a first differential scanning calorimetry measurement, which involves heating from -50°C to 200°C at a heating rate of 10°C / min (1st Run), an isothermal process where the temperature is maintained at 200°C for 5 minutes, and a cooling process from 200°C to -50°C at a cooling rate of 10°C / min (cooling measurement). The process involves holding the temperature at -50°C for 5 minutes, The second differential scanning calorimetry measurement consists of a process (2nd Run) in which the temperature is raised from -50°C to 200°C at a heating rate of 10°C / min, When you continue doing that, In DSC curve 2 (2nd Run) obtained by the second differential scanning calorimetry measurement, at least one endothermic peak is observed in each of the range of 100°C or higher and 140°C or lower and the range of 150°C or higher and 190°C or lower, In DSC curve 1 (1st Run) obtained by the first differential scanning calorimetry measurement, the heat of fusion calculated from the endothermic peak observed in the range of 0°C or higher and 140°C or lower is defined as ΔH 1st (J / g), In DSC curve 2 (2nd Run) obtained by the second differential scanning calorimetry measurement, the heat of fusion calculated from the endothermic peak observed in the range of 0°C or higher and 140°C or lower is defined as ΔH 2nd (J / g), ΔH 1st - ΔH 2nd is 1.0 J / g or more and 50.0 J / g or less, the barrier film. [2] The barrier film according to [1], wherein the ΔH 2nd is 205.0 J / g or less. [3] The barrier film according to [1] or [2], wherein the ΔH 1st is 210.0 J / g or less. [4] The barrier film according to any one of [1] to [3], comprising a layer containing an adhesive resin. [5] The density of the ethylene-based polymer in the polyethylene layer or the layer containing the adhesive resin, measured in accordance with JIS K 7112:1999, is 0.910 g / cm 3 or more and 0.970 g / cm 3 or less, the barrier film according to any one of [1] to [4]. [6] The tensile elastic modulus in the MD direction, measured in accordance with JIS K 7127:1999 using a tensile tester under the conditions of a measurement temperature of 23±2°C, 50±5%RH, and a tensile speed of 5 mm / min, is 600 MPa or more and 3300 MPa or less, the barrier film according to any one of [1] to [5]. [7] A barrier film as described in any of [1] to [6], wherein the thermal shrinkage rate in the MD direction after heat treatment at 120°C for 15 minutes, as measured in accordance with JIS C2151:2019, is 28.0% or less. [8] The water vapor transmission rate was measured according to Method 1 below in accordance with JIS Z 0208:1976, and when the thickness of the barrier film was converted to 20 μm, the transmission rate was 20.0 g / (m²). 2 A barrier film described in any of [1] to [7], which is less than or equal to ) days. (Method 1) The barrier film is folded in half, and two sides are heat-sealed to create an inner surface area of ​​0.01 m². 2 A bag is prepared so that 10 g of calcium chloride is placed inside the bag, the opening of the bag is heat-sealed, and the bag is then stored for 72 hours in an environment of 40°C and 90% RH humidity. The weight of the calcium chloride is measured before and after storage, and the water vapor transmission rate (g / m³) is calculated from the difference. 2 Calculate the day. [9] In accordance with JIS K7126:2006, measured under conditions of 20°C and 80% RH, the oxygen permeability when the thickness of the barrier resin layer is converted to 3 μm is 30.0 mL / (m²). 2 A barrier film as described in any of [1] to [8], having a pressure of less than or equal to (day·MPa).

[10] The polyethylene layer contains polyethylene as the ethylene polymer, A barrier film according to any one of [1] to [9], wherein when the entire polyethylene layer is considered to be 100% by mass, the polyethylene content in the polyethylene layer is 50% by mass or more.

[11] The barrier film according to any one of [1] to

[10] , wherein the barrier resin comprises one or more selected from the group consisting of ethylene-vinyl alcohol copolymer, polyvinyl alcohol resin, polyvinylidene chloride resin, polyamide resin, polyester resin, polyurethane resin, polycarboxylic acid resin, and a mixture containing a polycarboxylic acid resin, a polyamine resin, and a polyvalent metal compound.

[12] A barrier film according to any one of [1] to

[11] , wherein, when the entirety of the barrier resin layer is considered to be 100% by mass, the content of the barrier resin in the barrier resin layer is 50% by mass or more.

[13] A barrier film according to any of [1] to

[12] , which is a co-extruded film.

[14] A barrier film according to any one of [1] to

[13] , which is one selected from the group consisting of unoriented films, uniaxially oriented films, and biaxially oriented films.

[15] The barrier film according to any one of [1] to

[14] , wherein the barrier resin layer is not the outermost layer.

[16] The barrier film according to [4] to

[15] , wherein the adhesive resin comprises one or more selected from the group consisting of ethylene copolymers, acid-modified ethylene polymers, urethane resins, epoxy resins, and vinyl resins.

[17] The barrier film according to any one of [1] to

[16] , wherein the barrier film has one laminated structure selected from the group consisting of polyethylene layer / barrier resin layer / polyethylene layer and polyethylene layer / adhesive resin layer / barrier resin layer / adhesive resin layer / polyethylene layer.

[18] A barrier film according to any one of [1] to

[17] , wherein the tear strength in the MD direction of the barrier film, measured using a light-load tear tester under the following conditions: specimen size: MD direction: 63.5 mm, TD direction: 50.0 mm, tear length: 12.7 mm, and pendulum lift angle: 90°, is 15 mN or more and 3000 mN or less.

[19] A barrier film according to any of [1] to

[18] , wherein it cannot be peeled when the following method 2 is performed, or the peel strength measured by the following method 2 is 0.2 N / 15 mm or more. (Method 2) Using the barrier film cut to a width of 15 mm, the peel strength (N / 15 mm) between the polyethylene layer and the barrier resin layer is measured under the conditions of 23 ± 2°C, peel angle of 90°, peel speed of 300 mm / min, and tensile force in the MD direction.

[20] A barrier film according to any of [1] to

[19] , wherein the heat-sealing temperature at which the heat-sealing strength measured by method 3 below is 130°C or higher is 1.0 N / 15 mm or higher. (Method 3) Two 15mm wide strips of the barrier film are bonded together, then sandwiched between two 12μm thick biaxially oriented polyethylene terephthalate films. Finally, a heat seal tester is used to measure the temperature at 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C, and the pressure at 2.0 kgf / cm². 2 A laminated film is prepared by heat fusion under the condition of a sealing time of 1.0 second. Then, the two barrier films in the laminated film are peeled off under the conditions of 90° peeling, peeling speed of 300 mm / min, and tensile strength in the MD direction, and the peel strength at that time is defined as the heat fusion strength (N / 15 mm). [twenty one] A barrier film according to any one of [1] to

[20] , wherein the thickness of the barrier resin layer is 0.5 μm or more and 20.0 μm or less. [twenty two] A barrier film according to any one of [1] to

[21] , wherein the thickness of one polyethylene layer is 2.0 μm or more and 100.0 μm or less. [twenty three] A barrier film according to any one of [1] to

[22] , wherein the ratio of the thickness of the barrier resin layer to the total thickness of the barrier film is 1% or more and 30% or less. [twenty four] The barrier film according to any one of [1] to

[23] , wherein the content of the ethylene polymer in the barrier film is 50% by mass or more and 100% by mass or less when the total mass of the barrier film is considered to be 100% by mass. [twenty five] A barrier film described in any of [1] to

[24] , which is a packaging film.

[26] Packaging material containing a barrier film as described in any of [1] to

[25] .

[27]

[26] The packaging material described above, A package containing the article contained within the aforementioned packaging material. [Effects of the Invention]

[0010] According to the present invention, a barrier film with improved oxygen barrier properties can be provided. [Brief explanation of the drawing]

[0011] [Figure 1] This is a schematic cross-sectional view showing an example of the structure of the barrier film according to this embodiment. [Figure 2] This is a schematic cross-sectional view showing an example of the structure of the barrier film according to this embodiment. [Figure 3] This is a schematic cross-sectional view showing an example of the structure of the barrier film according to this embodiment. [Modes for carrying out the invention]

[0012] Embodiments of the present invention will be described below with reference to the drawings. Note that the drawings are schematic diagrams and do not correspond to the actual dimensional ratios. In this specification, unless otherwise specified, "A to B" indicating a numerical range means A or greater and B or less.

[0013] <Barrier film>

[0014] Figures 1-3 are schematic cross-sectional views showing an example of the barrier film 100 of this embodiment. As shown in Figures 1-3, the barrier film 100 of this embodiment comprises a polyethylene layer 101 and a barrier resin layer 102, wherein the polyethylene layer 101 contains an ethylene polymer and the barrier resin layer 102 contains a barrier resin, and the differential scanning calorimeter (DSC) is used to perform a first differential scanning calorimeter measurement consisting of a process of raising the temperature from -50°C to 200°C at a heating rate of 10°C / min (1st Run), an isothermal process of maintaining the temperature at 200°C for 5 minutes, a process of lowering the temperature from 200°C to -50°C at a cooling rate of 10°C / min (cooling measurement), and a process of maintaining the temperature at -50°C for 5 minutes. When a second differential scanning calorimetry (DSC) measurement is performed, consisting of a heating process from -50°C to 200°C at a heating rate of 10°C / min (2nd Run), at least one endothermic peak is observed in the range of 100°C to 140°C and the range of 150°C to 190°C in the DSC curve 2 (2nd Run) obtained from the second differential scanning calorimetry, and the heat of fusion calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 1 (1st Run) obtained from the first differential scanning calorimetry is ΔH 1st (J / g) is used, and the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 2 (2ndRun) obtained by the second differential scanning calorimetry, and is then given as ΔH. 2nd When (J / g), ΔH 1st -ΔH 2nd However, it is between 1.0 J / g and 50.0 J / g.

[0015] The present inventors have determined that in a barrier film 100 comprising a polyethylene layer and a barrier resin layer, at least one endothermic peak is observed in the DSC curve 2 (2nd Run) obtained by a second differential scanning calorimetry (DSC) measurement of the barrier film 100, in the range of 100°C to 140°C and the range of 150°C to 190°C, and the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 1 (1st Run) obtained by the first differential scanning calorimetry, and ΔH 1st(J / g) is used, and the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 2 (2ndRun) obtained by the second differential scanning calorimetry, and is then given as ΔH. 2nd When (J / g), ΔH 1st -ΔH 2nd We found that oxygen barrier properties can be improved by setting the range to a predetermined level.

[0016] In the barrier film 100 of this embodiment, when a differential scanning calorimeter (DSC) is used to perform a first differential scanning calorimeter measurement consisting of a heating process from -50°C to 200°C at a heating rate of 10°C / min (1st Run), an isothermal process of holding at 200°C for 5 minutes, a cooling process from 200°C to -50°C at a cooling rate of 10°C / min (cooling measurement), a holding at -50°C for 5 minutes, and a heating process from -50°C to 200°C at a heating rate of 10°C / min (2nd Run), at least one endothermic peak is observed in the DSC curve 2 (2nd Run) obtained from the second differential scanning calorimeter measurement, in both the range of 100°C to 140°C and the range of 150°C to 190°C. The observation of at least one endothermic peak in the range of 100°C to 140°C and the range of 150°C to 190°C in DSC curve 2 (2nd Run) indicates that the barrier film 100 of this embodiment contains a crystal structure with different melting point distributions, which is thought to further improve the oxygen barrier properties of the barrier film 100.

[0017] In the barrier film 100 of this embodiment, the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 1 (1st Run) obtained by the first differential scanning calorimetry, and is called ΔH. 1st (J / g) is used to determine the heat of fusion, which is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 2 (2ndRun) obtained from the second differential scanning calorimetry, and is expressed as ΔH. 2nd When (J / g), ΔH 1st -ΔH2nd The saturation is 1.0 J / g or more and 50.0 J / g or less, preferably 2.0 J / g or more and 45.0 J / g or less, more preferably 3.0 J / g or more and 45.0 J / g or less, even more preferably 4.0 J / g or more and 40.0 J / g or less, even more preferably 5.0 J / g or more and 35.0 J / g or less, and even more preferably 6.0 J / g or more and 30.0 J / g or less. ΔH 1st -ΔH 2nd Because the above range is maintained, the overall crystal structure of the barrier film 100 containing the ethylene polymer in the polyethylene layer 101 is more stable, and therefore the oxygen barrier properties of the barrier film 100 can be further improved.

[0018] In the barrier film 100 of this embodiment, ΔH 2nd Preferably, it is 205.0 J / g or less, more preferably 200.0 J / g or less, even more preferably 195.0 J / g or less, even more preferably 190.0 J / g or less, even more preferably 185.0 J / g or less, even more preferably 180.0 J / g or less, and even more preferably 175.0 J / g or less, and may also be, for example, 50.0 J / g or more, 80.0 J / g or more, or 100.0 J / g or more. Furthermore, in the barrier film 100 of this embodiment, ΔH 2nd It may be 50.0 J / g or more and 205.0 J / g or less, 50.0 J / g or more and 200.0 J / g or less, 80.0 J / g or more and 195.0 J / g or less, 80.0 J / g or more and 190.0 J / g or less, 80.0 J / g or more and 185.0 J / g or less, 100.0 J / g or more and 180.0 J / g or less, or 100.0 J / g or more and 175.0 J / g or less. ΔH 2nd By keeping the above upper limit below this value, the oxygen barrier properties of the barrier film 100 can be further suppressed.

[0019] In the barrier film 100 of this embodiment, ΔH 1stThe amount is preferably 210.0 J / g or less, more preferably 205.0 J / g or less, and even more preferably 200.0 J / g or less, and may also be, for example, 50.0 J / g or more, 80.0 J / g or more, or 100.0 J / g or more. Furthermore, in the barrier film 100 of this embodiment, ΔH 2nd This may be 50 J / g or more and 210.0 J / g or less, 80.0 J / g or more and 205.0 J / g or less, or 100.0 J / g or more and 200.0 J / g or less. ΔH 2nd By keeping the above upper limit below, the thermal dimensional stability of the barrier film 100 can be further suppressed.

[0020] In the barrier film 100 of this embodiment, the heat of fusion is calculated from the endothermic peak observed in the range of 150°C to 190°C in the DSC curve 1 (1st Run) obtained by the first differential scanning calorimetry, and is ΔH 1st(150-190) When (J / g), ΔH 1st(150-190) From the viewpoint of further improving the oxygen barrier properties of the barrier film 100, the oxygen level is preferably 5.0 J / g or more and 50.0 J / g or less, more preferably 6.0 J / g or more and 40.0 J / g or less, even more preferably 7.0 J / g or more and 30.0 J / g or less, and even more preferably 8.0 J / g or more and 20.0 J / g or less.

[0021] In the barrier film 100 of this embodiment, the heat of fusion is calculated from the endothermic peak observed in the range of 150°C to 190°C in the DSC curve 2 (2nd Run) obtained by the second differential scanning calorimetry, and is ΔH 2nd(150-190) When (J / g), ΔH 2nd(150-190) From the viewpoint of further improving the oxygen barrier properties of the barrier film 100, the oxygen level is preferably 5.0 J / g or more and 50.0 J / g or less, more preferably 6.0 J / g or more and 40.0 J / g or less, even more preferably 7.0 J / g or more and 30.0 J / g or less, and even more preferably 7.5 J / g or more and 20.0 J / g or less.

[0022] In the barrier film 100 of this embodiment, ΔH 1st(150-190) -ΔH 2nd(150-190) From the viewpoint of further improving the oxygen barrier properties of the barrier film 100, the oxygen level is preferably 0.3 J / g or more and 20.0 J / g or less, more preferably 0.5 J / g or more and 10.0 J / g or less, and even more preferably 0.7 J / g or more and 5.0 J / g or less.

[0023] In the barrier film 100, the heat of fusion (ΔH) obtained by differential scanning calorimetry is measured. 1st ΔH 2nd ΔH 1st(150-190) and ΔH 2nd(150-190) The following is how it is calculated: For the barrier film 100, a differential scanning calorimetry (DSC) is used to perform the following steps in succession: a first differential scanning calorimetry measurement consisting of a process of raising the temperature from -50°C to 200°C at a heating rate of 10°C / min (1st Run); an isothermal process of holding at 200°C for 5 minutes; a process of cooling from 200°C to -50°C at a cooling rate of 10°C / min (cooling measurement); a process of holding at -50°C for 5 minutes; and a second differential scanning calorimetry measurement consisting of a process of raising the temperature from -50°C to 200°C at a heating rate of 10°C / min (2nd Run). In the DSC curve 1 for the 1st Run, obtained from the first differential scanning calorimetry, the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C, which is ΔH. 1st (J / g) is used, and the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 2 (2ndRun) obtained by the second differential scanning calorimetry, and is then given as ΔH. 2nd Let's assume (J / g). Furthermore, in the DSC curve 1 obtained from the first differential scanning calorimetry, the heat of fusion is calculated from the endothermic peak observed in the range of 150°C to 190°C, which is ΔH. 1st(150-190) (J / g) is used, and the heat of fusion is calculated from the endothermic peak observed in the range of 150°C to 190°C in the DSC curve 2 (2ndRun) obtained by the second differential scanning calorimetry, and is then given as ΔH. 2nd(150-190) Let's assume (J / g). Here, the amount of heat of fusion for each endothermic peak is calculated by determining the area enclosed by the endothermic fusion curve containing each endothermic peak and the baseline. The baseline is defined as the line drawn by differentiating the Heat Flow with respect to time before and after the endothermic peak to display the Deriv. Heat Flow, and connecting the point where the change in Deriv. Heat Flow begins (i.e., the point where the flat region of Deriv. Heat Flow ends) and the point where the change in Deriv. Heat Flow ends (i.e., the point where Deriv. Heat Flow enters the flat region). Furthermore, if multiple endothermic peaks are observed within each temperature range, the largest peak will be considered the endothermic peak.

[0024] In the barrier film 100 of this embodiment, the tensile modulus T1 in the MD direction is preferably 600 MPa or more and 3300 MPa or less, more preferably 700 MPa or more and 3000 MPa or less, more preferably 800 MPa or more and 2900 MPa or less, even more preferably 1000 MPa or more and 2700 MPa or less, even more preferably 1200 MPa or more and 2500 MPa or less, and even more preferably 1400 MPa or more and 2400 MPa or less. If the tensile modulus T1 in the MD direction is above the lower limit, the balance of performance such as bag-making properties, thermal dimensional stability, heat resistance, film-forming properties, water vapor barrier properties, oxygen barrier properties, mechanical properties, transparency, handling properties, and packaging suitability can be further improved. If the tensile modulus T1 in the MD direction is below the upper limit, the balance of performance such as thermal dimensional stability, antistatic properties, bag-making properties, and packaging suitability can be further improved.

[0025] In the barrier film 100 of this embodiment, the tensile modulus T2 in the TD direction is preferably 600 MPa or more and 3300 MPa or less, more preferably 700 MPa or more and 3000 MPa or less, even more preferably 800 MPa or more and 2800 MPa or less, even more preferably 1000 MPa or more and 2600 MPa or less, even more preferably 1200 MPa or more and 2500 MPa or less, and even more preferably 1400 MPa or more and 2400 MPa or less. If the tensile modulus T2 in the TD direction is above the lower limit, the balance of performance such as bag-making properties, thermal dimensional stability, heat resistance, film-forming properties, water vapor barrier properties, oxygen barrier properties, mechanical properties, transparency, and handling properties can be further improved, and the stiffness of the barrier film 100 can be improved. If the tensile modulus in the TD direction is below the upper limit, problems such as cutting will be less likely to occur during film formation of the barrier film 100, continuous stretching and molding of the film will be easier, and industrial continuous productivity can be further improved.

[0026] In the barrier film 100 of this embodiment, the sum of the tensile modulus T1 in the MD direction and the tensile modulus T2 in the TD direction (T1+T2) is preferably 1000 MPa or more and 6000 MPa or less, more preferably 1500 MPa or more and 5700 MPa or less, even more preferably 2000 MPa or more and 5500 MPa or less, even more preferably 2500 MPa or more and 5000 MPa or less, and even more preferably 3000 MPa or more and 4800 MPa or less. If T1+T2 is above the lower limit, the balance of performance such as thermal dimensional stability, heat resistance, film-forming properties, water vapor barrier properties, oxygen barrier properties, mechanical properties, transparency, bag-making properties, and handling properties can be further improved, and the stiffness of the barrier film 100 can be improved. If T1+T2 is below the upper limit, problems such as cutting will be less likely to occur during film formation of the barrier film 100, continuous stretching and molding of the film will be easier, and industrial continuous productivity can be further improved.

[0027] The tensile modulus T1 in the MD direction and the tensile modulus T2 in the TD direction of the barrier film 100 are measured in accordance with JIS K7127:1999 using a tensile testing machine under the conditions of a measurement temperature of 23±2℃, 50±5%RH, and a tensile speed of 5mm / min.

[0028] In the barrier film 100 of this embodiment, the thermal shrinkage rate in the MD direction after heat treatment at 120°C for 15 minutes, as measured in accordance with JIS C2151:2019, is preferably 28.0% or less, preferably 25.0% or less, more preferably 23.0% or less, even more preferably 20.0% or less, even more preferably 18.0% or less, even more preferably 15.0% or less, even more preferably 13.0% or less, even more preferably 12.3% or less, even more preferably 12.0% or less, even more preferably 11.5% or less, even more preferably 11.0% or less, and even more preferably 10.5% or less, and may be 0.1% or more, 0.3% or more, 0.5% or more, and 0.8% or more. Furthermore, in the barrier film 100 of this embodiment, the thermal shrinkage rate in the MD direction when heat-treated at 120°C for 15 minutes, as measured in accordance with JIS C2151:2019, may be 0.1% or more and 28.0% or less, 0.1% or more and 25.0% or less, 0.1% or more and 23.0% or less, 0.3% or more and 20.0% or less, 0.3% or more and 18.0% or less, 0.3% or more and 15.0% or less, 0.5% or more and 13.0% or less, 0.5% or more and 12.3% or less, 0.5% or more and 12.0% or less, 0.8% or more and 11.5% or less, 0.8% or more and 11.0% or less, or 0.8% or more and 10.5% or less. By keeping the thermal shrinkage rate in the MD direction at 120°C below the above upper limit, thermal dimensional stability can be further improved. Furthermore, by keeping the thermal shrinkage rate in the MD direction at 120°C above the above lower limit, the balance between thermal dimensional stability and bag-making performance can be further improved.

[0029] In the barrier film 100 of this embodiment, the thermal shrinkage rate in the TD direction after heat treatment at 120°C for 15 minutes, as measured in accordance with JIS C2151:2019, is preferably 30.0% or less, more preferably 25.0% or less, even more preferably 20.0% or less, even more preferably 18.0% or less, even more preferably 15.0% or less, even more preferably 13.0% or less, even more preferably 11.0% or less, even more preferably 10.5% or less, even more preferably 10.0% or less, even more preferably 9.5% or less, and even more preferably 9.0% or less, and may be -5.0% or more, even if it is -3.0% or more, even if it is 0.0% or more, and may be 0.5% or more. Furthermore, in the barrier film 100 of this embodiment, the thermal shrinkage rate in the TD direction when heat-treated at 120°C for 15 minutes, as measured in accordance with JIS C2151:2019, may be -5.0% to 30.0%, -5.0% to 25.0%, -3.0% to 20.0%, -3.0% to 18.0%, -3.0% to 15.0%, 0.0% to 13.0%, 0.0% to 11.0%, 0.0% to 10.5%, 0.5% to 10.0%, 0.5% to 9.5%, or 0.5% to 9.0%. By keeping the thermal shrinkage rate in the TD direction at 120°C below the above upper limit, thermal dimensional stability can be improved. Furthermore, by keeping the thermal shrinkage rate in the TD direction at 120°C above the above lower limit, the balance between thermal dimensional stability and bag-making performance can be further improved. Furthermore, if the barrier film expands after being heated at 120°C for 15 minutes, the thermal shrinkage rate will be a negative value.

[0030] The thermal shrinkage rate of the barrier film 100 at 120°C in the MD and TD directions is measured in accordance with JIS C2151:2019 by the following method. A 10.00 cm x 10.00 cm test specimen is cut from barrier film 100. At this time, the test specimen is suspended in a constant temperature bath with hot air circulation without any force applied. Next, the test specimen is heat-treated at 120°C for 15 minutes. After the test specimen has cooled to room temperature, its length is measured. The length of the test specimen in the MD direction after heat treatment is measured as MD 120 Let the measurement be in [cm], and the thermal shrinkage rate in the MD direction [%] be 100 × (10.00 - MD 120 The length of the test specimen in the TD direction after heat treatment is calculated by ) / 10.00. 120 Let the measurement be in [cm], and the thermal shrinkage rate in the TD direction [%] be 100 × (10.00 - TD 120 Calculated by ) / 10.00.

[0031] In the barrier film 100 of this embodiment, the water vapor transmission rate when the thickness of the barrier film 100 is converted to 20 μm is preferably 20.0 g / (m²). 2 • day) or less, more preferably 19.0 g / (m 2 • day) or less, more preferably 18.0 g / (m 2 • day) or less, more preferably 17.0 g / (m 2 • day) or less, more preferably 15.0 g / (m 2 • day) or less, more preferably 13.0 g / (m 2 • day) or less, more preferably 11.0 g / (m 2 • day) or less, more preferably 10.0 g / (m 2 • day) or less, more preferably 9.0 g / (m 2 • day) or less, more preferably 8.0 g / (m 2 It is less than or equal to (day). By keeping the water vapor transmission rate below the above upper limit when the barrier film 100 is converted to a thickness of 20 μm, the water vapor barrier properties can be further improved. Since a lower water vapor transmission rate for the barrier film 100 is preferable, the lower limit is not particularly limited. However, when the barrier film 100 is converted to a thickness of 20 μm, the water vapor transmission rate is, for example, 0.1 g / (m²). 2 • day) or more, 0.5g / (m2 ·day) or more, and may be 1.0 g / (m 2 ·day) or more. Further, in the barrier film 100 of the present embodiment, the water vapor transmission rate when the thickness of the barrier film 100 is converted to 20 μm may be 0.1 g / (m 2 ·day) or more and 20.0 g / (m 2 ·day) or less, may be 0.1 g / (m 2 ·day) or more and 19.0 g / (m 2 ·day) or less, may be 0.1 g / (m 2 ·day) or more and 18.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 17.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 15.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 13.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 11.0 g / (m 2 ·day) or less, may be 1.0 g / (m 2 ·day) or more and 10.0 g / (m 2 ·day) or less, may be 1.0 g / (m 2 ·day) or more and 9.0 g / (m 2 ·day) or less, may be 1.0 g / (m 2 ·day) or more and 8.0 g / (m 2 ·day) or less.

[0032] In the barrier film 100 of the present embodiment, the water vapor transmission rate is preferably 17.0 g / (m 2 ·day) or less, more preferably 16.0 g / (m 2 ·day) or less, still more preferably 15.0 g / (m 2 ·day) or less, still more preferably 14.0 g / (m 2 ·day) or less, still more preferably 13.0 g / (m2 ·day) or less, more preferably 12.0 g / (m 2 ·day) or less, more preferably 11.0 g / (m 2 ·day) or less, more preferably 9.0 g / (m 2 ·day) or less, more preferably 7.0 g / (m 2 ·day) or less, more preferably 5.0 g / (m 2 ·day) or less. By setting the water vapor permeability of the barrier film 100 to be equal to or less than the above upper limit value, the water vapor barrier property can be further improved. Since a lower water vapor permeability of the barrier film 100 is more preferable, the lower limit value is not particularly limited, and the water vapor permeability is, for example, 0.1 g / (m 2 ·day) or more, may be 0.5 g / (m 2 ·day) or more, or may be 1.0 g / (m 2 ·day) or more. Further, in the barrier film 100 of the present embodiment, the water vapor permeability may be 0.1 g / (m 2 ·day) or more and 17.0 g / (m 2 ·day) or less, may be 0.1 g / (m 2 ·day) or more and 16.0 g / (m 2 ·day) or less, may be 0.1 g / (m 2 ·day) or more and 15.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 14.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 13.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 12.0 g / (m 2 ·day) or less, may be 0.5 g / (m 2 ·day) or more and 11.0 g / (m 2 ·day) or less, may be 1.0 g / (m 2 ·day) or more and 9.0 g / (m 2 ·day) or less, may be 1.0 g / (m2 ·day) or more than 7.0g / (m 2 It may be less than or equal to 1.0g / (m 2 ·day) or more 5.0g / (m 2 It may be less than or equal to the following day.

[0033] The water vapor transmission rate of barrier film 100 is measured by the following method in accordance with JIS Z 0208:1976. (Method 1) The barrier film 100 is folded in half, and two sides are heat-sealed to create an inner surface area of ​​0.01 m². 2 A bag is prepared as follows: 10g of calcium chloride is placed inside the bag, the opening of the bag is heat-sealed, and then the bag is stored for 72 hours in an environment of 40°C and 90% RH humidity. The weight of calcium chloride is measured before and after storage, and the water vapor transmission rate (g / m³) is calculated from the difference. 2 Calculate the day. From the obtained water vapor transmission rate and the thickness of the barrier film 100 used in the measurement, the water vapor transmission rate when the barrier film 100 is converted to a thickness of 20 μm is calculated.

[0034] In the barrier film 100 of this embodiment, the oxygen permeability measured under conditions of 20°C and 80%RH in accordance with JIS K7126:2006, when the thickness of the barrier resin layer 102 is converted to 3 μm, is preferably 30.0 mL / (m²). 2 (·day·MPa) or less, more preferably 27.0 mL / (m³) 2 (·day·MPa) or less, more preferably 25.0 mL / (m²) 2 (·day·MPa) or less, more preferably 20.0 mL / (m²) 2 (·day·MPa) or less, more preferably 15.0 mL / (m²) 2 (·day·MPa) or less, more preferably 10.0 mL / (m²) 2 It is less than or equal to (·day·MPa). By setting the oxygen permeability within the above range when the thickness of the barrier resin layer 102 is converted to 3 μm, the oxygen barrier properties can be further improved. Since a lower oxygen permeability of the barrier film 100 is preferable, the lower limit is not particularly limited. However, when the thickness of the barrier resin layer 102 is converted to 3 μm, the oxygen permeability is, for example, 0.1 mL / (m²). 2 (·day·MPa) or higher, and 1.0 mL / (m 2 It may be 3.0 mL / (m³) or higher, and 3.0 mL / (m³) 2 It may be above (·day·MPa). Furthermore, in the barrier film 100 of this embodiment, the oxygen permeability measured under conditions of 20°C and 80%RH in accordance with JIS K7126:2006, when the thickness of the barrier resin layer 102 is converted to 3 μm, is 0.1 mL / (m²). 2 (·day·MPa) or more 30.0 mL / (m 2 It may be less than or equal to (·day·MPa), and 0.1 mL / (m 2 (·day·MPa) 27.0 mL / (m 2 It may be less than or equal to 1.0 mL / (m³) 2 (·day·MPa) or more 25.0 mL / (m 2 It may be less than or equal to 1.0 mL / (m³) 2 (·day·MPa) or more 20.0 mL / (m 2 It may be less than or equal to 3.0 mL / (m³) 2 (·day·MPa) or more than 15.0 mL / (m 2 It may be less than or equal to 3.0 mL / (m³) 2 (·day·MPa) or more than 10.0 mL / (m 2 It may also be below (·day·MPa). Furthermore, the oxygen permeability B when the thickness of the barrier resin layer 102 is converted to 3 μm is calculated from the thickness a of the barrier resin layer and the measured oxygen permeability A using the following formula (1). Equation (1) Oxygen permeability B [mL / (m²)] converted to a thickness of 3 μm 2 (Day·MPa) = (Barrier resin layer thickness a [μm] / 3 [μm]) × Oxygen permeability measurement value A [mL / (m 2 (·day·MPa)

[0035] In the barrier film 100 of this embodiment, the oxygen permeability measured under conditions of 20°C and 80%RH in accordance with JIS K7126:2006 is preferably 40.0 mL / (m²). 2 (·day·MPa) or less, more preferably 35.0 mL / (m²) 2 (·day·MPa) or less, more preferably 30.0 mL / (m²) 2 (·day·MPa) or less, more preferably 25.0 mL / (m²) 2 (·day·MPa) or less, more preferably 20.0 mL / (m²) 2 (·day·MPa) or less, more preferably 15.0 mL / (m²) 2 It is less than or equal to (·day·MPa). By setting the oxygen permeability of the barrier film 100 within the above range, the oxygen barrier properties can be further improved. Since a lower oxygen permeability of the barrier film 100 is preferable, the lower limit is not particularly limited, but the oxygen permeability is, for example, 0.1 mL / (m²). 2 (·day·MPa) or higher, and 1.0 mL / (m 2 It may be 1.5 mL / (m³) or higher, and 1.5 mL / (m³) 2 It may be above (·day·MPa). Furthermore, in the barrier film 100 of this embodiment, the oxygen permeability measured under conditions of 20°C and 80%RH in accordance with JIS K7126:2006 is 0.1 mL / (m²). 2 (·day·MPa) or more 40.0 mL / (m 2 It may be less than or equal to (·day·MPa), and 0.1 mL / (m 2 (·day·MPa) or more than 35.0 mL / (m 2 It may be less than or equal to 1.0 mL / (m³) 2 (·day·MPa) or more 30.0 mL / (m 2 It may be less than or equal to 1.0 mL / (m³) 2 (·day·MPa) or more 25.0 mL / (m 2 It may be less than or equal to 2.0 mL / (m³) 2 (·day·MPa) or more 20.0 mL / (m 2It may be less than or equal to 2.0 mL / (m³) 2 (·day·MPa) or more than 15.0 mL / (m 2 It may also be below (·day·MPa).

[0036] In the barrier film 100 of this embodiment, the tear strength in the MD direction is preferably 15 mN or more and 3000 mN or less, more preferably 15 mN or more and 2000 mN or less, even more preferably 18 mN or more and 1000 mN or less, even more preferably 18 mN or more and 500 mN or less, even more preferably 20 mN or more and 300 mN or less, even more preferably 23 mN or more and 200 mN or less, and even more preferably 25 mN or more and 150 mN or less. By ensuring that the tear strength in the MD direction is above the lower limit, the balance between film-forming properties and bag-making processability can be further improved. Furthermore, by ensuring that the tear strength in the MD direction is below the upper limit, tear resistance can be further improved while maintaining heat-sealability and rigidity.

[0037] In the barrier film 100 of this embodiment, the tear strength in the TD direction is preferably 15 mN or more and 3000 mN or less, more preferably 20 mN or more and 2000 mN or less, even more preferably 25 mN or more and 1000 mN or less, even more preferably 30 mN or more and 800 mN or less, even more preferably 35 mN or more and 500 mN or less, even more preferably 40 mN or more and 300 mN or less, and even more preferably 45 mN or more and 200 mN or less. By ensuring that the tear strength in the TD direction is above the lower limit, the balance between film-forming properties and bag-making processability can be further improved. Furthermore, by ensuring that the tear strength in the TD direction is below the upper limit, tear resistance can be further improved while maintaining heat-sealability and rigidity.

[0038] The tear strength in the MD and TD directions of the barrier film 100 is measured by the following method. Using a light-load tear tester, the tear strength in the MD direction was measured under the following conditions: specimen size: MD direction: 63.5 mm, TD direction: 50.0 mm, tear length: 12.7 mm, pendulum lift angle: 90°, by appropriately combining pendulum weights from 16 g to 720 g according to the measurement load range. Furthermore, using a light-load tear tester, under the conditions of specimen size: MD direction: 63.5 mm, TD direction: 50.0 mm, tear length: 12.7 mm, pendulum lift angle: 90°, the tear strength (mN) in the TD direction is measured by appropriately combining pendulum weights from 16 g to 720 g according to the measurement load range.

[0039] In the barrier film 100 of this embodiment, it is preferable that the polyethylene layer 101 and the barrier resin layer 102 cannot be separated when the peel strength is measured. Also, if the polyethylene layer 101 and the barrier resin layer 102 can be separated when the peel strength is measured in the barrier film 100, the peel strength is preferably 0.2 N / 15 mm or more, more preferably 0.3 N / 15 mm or more, even more preferably 0.4 N / 15 mm or more, and even more preferably 0.5 N / 15 mm or more. By having a peel strength equal to or greater than the above lower limit, the bonding between the polyethylene layer 101 and the barrier resin layer 102 can be improved, and the barrier properties and bag-making processability of the barrier film 100 can be further enhanced. Since a higher peel strength of the barrier film 100 is preferable, the upper limit is not particularly limited, but the peel strength may be, for example, 20 N / 15 mm or less, 18 N / 15 mm or less, or 15 N / 15 mm or less.

[0040] The peel strength of the barrier film 100 is measured by the following method. (Method 2) Using a barrier film 100 cut to a width of 15 mm, the peel strength (N / 15 mm) between the polyethylene layer 101 and the barrier resin layer 102 is measured under the conditions of 23 ± 2°C, peel angle of 90°, peel speed of 300 mm / min, and tensile strength in the MD direction.

[0041] In the barrier film 100 of this embodiment, the heat-sealing temperature at which the heat-sealing strength when two polyethylene layers 101 of the barrier film 100 are heat-sealed together to form a bond of 1.0 N / 15 mm or more is preferably 130°C or higher, more preferably 135°C or higher, even more preferably 140°C or higher, and for example, 150°C or lower, from the viewpoint of further improving the balance of performance in blocking resistance, heat resistance, and bag-making processability. Furthermore, the heat-sealing temperature at which the heat-sealing strength of 1.0 N / 15 mm or more is achieved when the polyethylene layers 101 of two barrier films 100 are heat-sealed together may be 130°C to 150°C, 135°C to 150°C, or 140°C to 150°C, from the viewpoint of further improving the balance of performance in blocking resistance, heat resistance, and bag-making processability.

[0042] The heat-sealing strength of the barrier film 100 is measured by the following method. (Method 3) Two polyethylene layers 101 of barrier film 100, cut to a width of 15 mm, are bonded together, then sandwiched between two 12 μm thick biaxially oriented polyethylene terephthalate films, and then tested using a heat seal tester at temperatures of 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C, and at a pressure of 2.0 kgf / cm². 2 A laminated film is prepared by heat fusion under the condition of a sealing time of 1.0 second. Then, under the conditions of 90° peeling, peeling speed of 300 mm / min, and tensile strength in the MD direction, the two barrier films 100 in the laminated film are peeled off one by one, and the peel strength at that time is defined as the heat fusion strength (N / 15 mm).

[0043] The following describes each layer that makes up the barrier film 100.

[0044] As shown in Figure 1, the barrier film 100 of this embodiment comprises a polyethylene layer 101 and a barrier resin layer 102. The polyethylene layer 101 may be a single layer or a layer consisting of two or more layers, preferably two layers. The barrier resin layer 102 may be a single layer or a layer consisting of two or more layers, and is preferably a single layer. Furthermore, the barrier resin layer 102 may be the outermost layer or an intermediate layer, but from the viewpoint of further improving the balance between barrier properties and film-forming properties, it is preferable that the barrier resin layer 102 is not the outermost layer in the barrier film 100, and more preferably an intermediate layer. Also from the viewpoint of further improving the balance between barrier properties and film-forming properties, it is preferable to have polyethylene layers 101 on both sides of the barrier resin layer 102, as shown in Figure 2.

[0045] When the barrier film 100 comprises polyethylene layers 101 on both sides of a barrier resin layer 102, the two polyethylene layers 101 may be made of the same material or different materials, but from the viewpoint of further improving productivity, it is preferable that the two polyethylene layers 101 be made of the same material. Furthermore, the thicknesses of the two polyethylene layers 101 may be the same or different, but from the viewpoint of further improving productivity, it is preferable that the thicknesses of the two polyethylene layers 101 be the same.

[0046] As shown in Figure 3, the barrier film 100 of this embodiment preferably has a layer 103 containing an adhesive resin (hereinafter also referred to as the adhesive resin layer 103). This improves the adhesion between the polyethylene layer 101 and the barrier resin layer 102, thereby further improving the barrier properties and suitability for bag making of the barrier film 100.

[0047] The barrier film 100 of this embodiment preferably has one laminated structure selected from the group consisting of polyethylene layer 101 / barrier resin layer 102, polyethylene layer 101 / barrier resin layer 102 / polyethylene layer 101, and polyethylene layer 101 / adhesive resin layer 103 / barrier resin layer 102 / adhesive resin layer 103 / polyethylene layer 101, more preferably has one laminated structure selected from the group consisting of polyethylene layer 101 / barrier resin layer 102 / polyethylene layer 101, and polyethylene layer 101 / adhesive resin layer 103 / barrier resin layer 102 / adhesive resin layer 103 / polyethylene layer 101, and even more preferably has a laminated structure of polyethylene layer 101 / adhesive resin layer 103 / barrier resin layer 102 / adhesive resin layer 103 / polyethylene layer 101.

[0048] In the case of a three-layer structure consisting of polyethylene layer 101 / barrier resin layer 102 / polyethylene layer 101, the polyethylene layer 101 may also serve as the adhesive resin layer 103 by containing an adhesive resin. That is, the barrier film 100 may have a laminated structure of an ethylene copolymer and adhesive resin blend layer / barrier resin layer 102 / ethylene copolymer and adhesive resin blend layer.

[0049] Furthermore, in the case of a five-layer structure consisting of polyethylene layer 101 / adhesive resin layer 103 / barrier resin layer 102 / adhesive resin layer 103 / polyethylene layer 101, the adhesive resin layer 103 may contain an ethylene polymer. That is, the barrier film 100 may have a laminated structure consisting of polyethylene layer 101 / blend layer of ethylene copolymer and adhesive resin / barrier resin layer 102 / blend layer of ethylene copolymer and adhesive resin / polyethylene layer 101.

[0050] The laminated structure of polyethylene layer 101 / adhesive resin layer 103 / barrier resin layer 102 / adhesive resin layer 103 / polyethylene layer 101 is specifically shown in Figure 3. By having a laminated structure of five layers consisting of polyethylene layer 101 / adhesive resin layer 103 / barrier resin layer 102 / adhesive resin layer 103 / polyethylene layer 101, the adhesive resin content in the entire barrier film 100 can be reduced further compared to the case where polyethylene layer 101 also serves as the adhesive resin layer 103 as described above, while further improving the adhesion between polyethylene layer 101 and adhesive resin layer 103, and consequently improving the balance of barrier properties and bag-making properties.

[0051] Furthermore, even when the barrier film 100 has a three-layer structure and the polyethylene layer 101 also serves as the adhesive resin layer 103, or when the barrier film 100 has a five-layer structure, it is preferable that the adhesive resin layer 103 is in direct contact with the barrier resin layer 102. This further improves the adhesion between the polyethylene layer 101 and the barrier resin layer 102.

[0052] The thickness of the polyethylene layer 101 is preferably 2.0 μm or more and 100.0 μm or less, more preferably 3.0 μm or more and 80.0 μm or less, even more preferably 5.0 μm or more and 50.0 μm or less, and even more preferably 6.0 μm or more and 20.0 μm or less. When the barrier film 100 has a two-layer structure consisting of a polyethylene layer 101 and a barrier resin layer 102, the thickness of the polyethylene layer 101 is preferably 5.0 μm or more and 100.0 μm or less, more preferably 10.0 μm or more and 90.0 μm or less, even more preferably 30.0 μm or more and 80.0 μm or less, and even more preferably 40.0 μm or more and 50.0 μm or less. When the barrier film 100 has a three-layer structure consisting of a polyethylene layer 101, a barrier resin layer 102, and another polyethylene layer 101, the thickness of the polyethylene layer 101 is preferably 3.0 μm or more and 100.0 μm or less, more preferably 4.0 μm or more and 80.0 μm or less, even more preferably 5.0 μm or more and 50.0 μm or less, and even more preferably 6.0 μm or more and 30.0 μm or less. When the barrier film 100 has a five-layer structure consisting of a polyethylene layer 101, an adhesive resin layer 103, a barrier resin layer 102, an adhesive resin layer 103, and a polyethylene layer 101, the thickness of the polyethylene layer 101 is preferably 2.0 μm or more and 100.0 μm or less, more preferably 3.0 μm or more and 80.0 μm or less, even more preferably 4.0 μm or more and 50.0 μm or less, even more preferably 5.0 μm or more and 30.0 μm or less, and even more preferably 6.0 μm or more and 20.0 μm or less. Note that the thickness of the polyethylene layer 101 mentioned above represents the thickness of one polyethylene layer 101. By setting the thickness of the polyethylene layer 101 within the above range, the balance of performance characteristics of the barrier film 100, such as thermal dimensional stability, film-forming properties, water vapor barrier properties, oxygen barrier properties, cost, mechanical properties, transparency, bag-making properties, handling properties, appearance, and lightweight properties, can be further improved.

[0053] The thickness of the barrier resin layer 102 is preferably 0.5 μm to 20.0 μm, more preferably 1.0 μm to 15.0 μm, even more preferably 1.5 μm to 10.0 μm, and even more preferably 2.0 μm to 8.0 μm. By setting the thickness of the barrier resin layer 102 to be greater than or equal to the lower limit, the barrier properties of the polyethylene layer 101 and the barrier resin layer 102 can be further improved. Furthermore, by setting the thickness of the barrier resin layer 102 to be less than or equal to the upper limit, the barrier resin content can be further reduced, thereby further improving the recyclability of the barrier film 100. By setting the thickness of the barrier resin layer 102 within the above range, the balance of performance aspects such as thermal dimensional stability, film-forming properties, cost, mechanical properties, transparency, bag-making properties, handling properties, appearance, and lightweight properties of the barrier film 100 can be further improved.

[0054] The ratio of the thickness of the barrier resin layer 102 to the total thickness of the barrier film 100 is preferably 1% to 30%, more preferably 3% to 25%, even more preferably 5% to 20%, even more preferably 10% to 18%, and even more preferably 12% to 16%. By setting the ratio of the thickness of the barrier resin layer 102 to the total thickness of the barrier film 100 to be above the lower limit, the barrier properties of the polyethylene layer 101 and the barrier resin layer 102 can be further improved. Furthermore, by setting the ratio of the thickness of the barrier resin layer 102 to the total thickness of the barrier film 100 to be below the upper limit, the amount of barrier resin can be further reduced, thereby further improving the recyclability of the barrier film 100. This allows for a further improvement in the balance of performance characteristics of the barrier film 100, including thermal dimensional stability, film-forming properties, cost, mechanical properties, transparency, bag-making properties, handling properties, appearance, and lightweight properties.

[0055] The thickness of the adhesive resin layer 103 is preferably 0.5 μm or more and 10.0 μm or less, more preferably 0.8 μm or more and 8.0 μm or less, and preferably 1.0 μm or more and 5.0 μm or less. By setting the thickness of the adhesive resin layer 103 to be greater than or equal to the lower limit, the adhesion between the polyethylene layer 101 and the barrier resin layer 102 can be further improved. Furthermore, by setting the thickness of the adhesive resin layer 103 to be less than or equal to the upper limit, the content of the adhesive resin can be further reduced, thereby further improving the recyclability of the barrier film 100. The thickness of the adhesive resin layer 103 refers to the thickness of the adhesive resin layer 103 in cases other than when the barrier film 100 has a three-layer structure and the polyethylene layer 101 also serves as the adhesive resin layer 103.

[0056] The overall thickness of the barrier film 100 is preferably 3.0 μm to 130.0 μm, more preferably 5.0 μm to 100.0 μm, even more preferably 8.0 μm to 80.0 μm, even more preferably 10.0 μm to 60.0 μm, and even more preferably 13.0 μm to 50.0 μm. By setting the overall thickness of the barrier film 100 within the above range, the balance of performance such as thermal dimensional stability, heat resistance, film-forming properties, water vapor barrier properties, oxygen barrier properties, cost, mechanical properties, transparency, bag-making properties, handling properties, appearance, and lightweight properties can be further improved.

[0057] The density of barrier film 100, measured in accordance with JIS K 7112:1999, is preferably 0.960 g / cm³. 3 More than 1.000g / cm 3 More preferably, 0.965 g / cm³ 3 More than 0.998g / cm 3 More preferably, 0.970 g / cm³ 3 More than 0.995g / cm 3 The following applies: By setting the density of the barrier film 100 to or above the lower limit, the balance of various properties such as bag-making properties, barrier properties, thermal dimensional stability, film-forming properties, heat resistance, mechanical properties, and rigidity of the barrier film 100 can be further improved. Furthermore, by setting the density of the barrier film 100 to or below the upper limit, the film-forming properties of the barrier film 100 can be further improved. The density of the barrier film 100 represents the total density of the polyethylene layer 101, the barrier resin layer 102, and the layer 103 containing adhesive resin that make up the barrier film 100.

[0058] [Polyethylene layer] The polyethylene layer 101 contains an ethylene polymer. The ethylene-based polymer preferably contains polyethylene, more preferably one or more selected from the group consisting of high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE), and linear low-density polyethylene (LLDPE), more preferably one or more selected from the group consisting of high-density polyethylene (HDPE), medium-density polyethylene (MDPE), and linear low-density polyethylene (LLDPE), even more preferably one or more selected from the group consisting of high-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE), and even more preferably high-density polyethylene (HDPE). This makes it possible to further improve the balance of various properties of the barrier film 100, such as thermal dimensional stability, film-forming properties, heat resistance, water vapor barrier properties, oxygen barrier properties, mechanical properties, and rigidity. Here, low-density polyethylene (LDPE) refers to 0.910 g / cm³. 3 More than 0.930g / cm 3 This refers to polyethylene with a density of less than 0.930 g / cm³, and medium-density polyethylene (MDPE) is defined as having a density of 0.930 g / cm³. 3 More than 0.942g / cm 3 This refers to polyethylene with a density of less than 0.942 g / cm³, and high-density polyethylene (HDPE) is defined as 0.942 g / cm³. 3 This term refers to polyethylene having the above density. Furthermore, low-density polyethylene and medium-density polyethylene with few branched structures are referred to as linear low-density polyethylene (LLDPE).

[0059] In this embodiment, the ethylene polymer in the barrier film 100 is a concept that also includes the acid-modified ethylene polymer in the adhesive resin described later, and the ethylene-vinyl alcohol copolymer in the barrier resin.

[0060] The density of the ethylene polymer in the polyethylene layer 101 or the layer 103 containing the adhesive resin in this embodiment, as measured in accordance with JIS K 7112:1999, is preferably 0.910 g / cm³. 3 More than 0.970g / cm 3 More preferably, 0.915 g / cm³3 More than 0.970g / cm 3 More preferably, 0.920 g / cm³ 3 More than 0.965g / cm 3 More preferably, 0.925 g / cm³ 3 More than 0.965g / cm 3 More preferably, 0.930 g / cm³ 3 More than 0.960g / cm 3 More preferably, 0.935 g / cm³ 3 More than 0.960g / cm 3 More preferably, 0.940 g / cm³ 3 More than 0.955g / cm 3 More preferably, 0.942 g / cm³ 3 More than 0.955g / cm 3 The following applies: By setting the density of the ethylene polymer above the lower limit mentioned above, the balance of various properties of the barrier film 100, such as thermal dimensional stability, film-forming properties, heat resistance, mechanical properties, and rigidity, can be further improved. Conversely, by setting the density of the ethylene polymer below the upper limit mentioned above, the film-forming properties of the barrier film 100 can be further improved. The density of the ethylene polymer mentioned above represents the density including the adhesive resin when the barrier film 100 has a layer 103 containing the adhesive resin.

[0061] The density of the polyethylene layer 101, measured in accordance with JIS K 7112:1999, is preferably 0.910 g / cm³. 3 More than 0.970g / cm 3 More preferably, 0.915 g / cm³ 3 More than 0.970g / cm 3 More preferably, 0.920 g / cm³ 3 More than 0.965g / cm 3 More preferably, 0.925 g / cm³ 3 More than 0.965g / cm 3 More preferably, 0.930 g / cm³ 3 More than 0.960g / cm 3 More preferably, 0.935 g / cm³ 3More than 0.960g / cm 3 More preferably, 0.940 g / cm³ 3 More than 0.955g / cm 3 More preferably, 0.942 g / cm³ 3 More than 0.955g / cm 3 The following applies: By setting the density of the polyethylene layer 101 to above the lower limit, the balance of various properties of the barrier film 100, such as thermal dimensional stability, film-forming properties, heat resistance, mechanical properties, and rigidity, can be further improved. Conversely, by setting the density of the polyethylene layer 101 to below the upper limit, the film-forming properties of the barrier film 100 can be further improved.

[0062] In accordance with JIS K 7210:1999, the melt mass flow rate (MFR) of the ethylene polymer in the polyethylene layer 101 or the layer 103 containing the adhesive resin of this embodiment, measured under conditions of 190°C and a 2160g load, is preferably 0.01g / 10min to 50g / 10min, more preferably 0.05g / 10min to 30g / 10min, even more preferably 0.1g / 10min to 10g / 10min, even more preferably 0.2g / 10min to 5g / 10min, and even more preferably 0.3g / 10min to 3g / 10min, from the viewpoint of further improving the balance of performance in terms of fluidity, film-forming ability and thermal dimensional stability.

[0063] The melting point of the ethylene polymer in the polyethylene layer 101 or the layer 103 containing the adhesive resin of this embodiment, as measured by differential scanning calorimeter (DSC), is preferably 100°C to 170°C, more preferably 110°C to 150°C, and even more preferably 120°C to 135°C, from the viewpoint of further improving the balance of performance such as film-forming ability, thermal dimensional stability, heat resistance, water vapor barrier properties, oxygen barrier properties, mechanical properties, rigidity, bag-making ability, and fluidity.

[0064] The polyethylene layer 101 preferably contains polyethylene as an ethylene polymer, and when the total polyethylene layer 101 is considered to be 100% by mass, the polyethylene content in the polyethylene layer 101 is preferably 50% by mass or more and 100% by mass or less, more preferably 80% by mass or more and 100% by mass or less, even more preferably 85% by mass or more and 100% by mass or less, even more preferably 90% by mass or more and 100% by mass or less, even more preferably 95% by mass or more and 100% by mass or less, and even more preferably 98% by mass or more and 100% by mass or less. When the total polyethylene layer 101 is considered to be 100% by mass, by setting the polyethylene content in the polyethylene layer 101 to be above the lower limit value above, the balance of various performances of the barrier film 100, such as thermal dimensional stability, film-forming properties, heat resistance, mechanical properties, and rigidity, can be further improved. Also, when the total polyethylene layer 101 is considered to be 100% by mass, by setting the polyethylene content in the polyethylene layer 101 to be below the upper limit value above, the balance of processability and continuous productivity of the barrier film 100 can be further improved.

[0065] From the viewpoint of further improving recyclability, the content of ethylene polymer in the barrier film 100 is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more, when the total amount of the barrier film 100 is considered as 100% by mass. The ethylene polymer content in the barrier film 100 is desirable as long as it is high, so there is no particular upper limit. However, it may be, for example, 100% by mass or less, 99.9% by mass or less, or 99.5% by mass or less. Furthermore, from the viewpoint of further improving recyclability, the ethylene polymer content in the barrier film 100 may be 50% to 100% by mass, 60% to 100% by mass, 70% to 99.9% by mass, 80% to 99.9% by mass, 90% to 99.5% by mass, or 95% to 99.5% by mass, when the total amount of the barrier film 100 is considered to be 100% by mass. As a result, since the barrier film 100 is composed almost entirely of a single material (monomaterial), the work required to separate the materials that make up the barrier film 100 is reduced, and the recyclability of the barrier film 100 can be further improved.

[0066] (Other ingredients) The polyethylene layer 101 may optionally contain various additives such as tackifiers, heat stabilizers, weather stabilizers, antioxidants, UV absorbers, lubricants, slip agents, nucleating agents, antiblocking agents, antistatic agents, antifogging agents, pigments, dyes, and inorganic or organic fillers, to the extent that they do not impair the purpose of this embodiment.

[0067] [Barrier resin layer] The barrier resin layer 102 contains a barrier resin. When the entire barrier resin layer 102 is considered to be 100% by mass, the content of the barrier resin in the barrier resin layer 102 is preferably 50% by mass or more and 100% by mass or less, more preferably 60% by mass or more and 100% by mass or less, even more preferably 70% by mass or more and 100% by mass or less, even more preferably 80% by mass or more and 100% by mass or less, and even more preferably 90% by mass or more and 100% by mass or less. By ensuring that the barrier resin content in the barrier resin layer 102 is equal to or greater than the above lower limit, when the entire barrier resin layer 102 is considered as 100% by mass, the barrier properties of the barrier film 100 can be further improved. By ensuring that the barrier resin content in the barrier resin layer 102 is equal to or less than the above upper limit, when the entire barrier resin layer 102 is considered as 100% by mass, the balance between the processability and continuous productivity of the barrier film 100 can be further improved.

[0068] The barrier resin preferably comprises one or more selected from the group consisting of ethylene-vinyl alcohol copolymer, polyvinyl alcohol resin, polyvinylidene chloride resin, polyamide resin, polyester resin, polyurethane resin, polycarboxylic acid resin, and mixtures containing polycarboxylic acid resin, polyamine resin, and polyvalent metal compound, and more preferably comprises ethylene-vinyl alcohol copolymer. This further improves the barrier properties of the barrier film 100. Furthermore, since ethylene-vinyl alcohol copolymer is an ethylene-based polymer, it can be recycled together with polyethylene. Therefore, including ethylene-vinyl alcohol copolymer in the barrier resin can further improve the recyclability of the barrier film 100 when it is recycled. Furthermore, because the ethylene-vinyl alcohol copolymer has excellent stretchability, productivity can be further improved even when the polyethylene layer 101 and the barrier resin layer 102 are stretched simultaneously.

[0069] (Ethylene-vinyl alcohol copolymer) Ethylene-vinyl alcohol copolymer is a copolymer of ethylene and vinyl alcohol. When the total content of constituent units constituting the ethylene-vinyl alcohol copolymer is set to 100 mol%, the content of constituent units derived from ethylene in the ethylene-vinyl alcohol copolymer is preferably 5 mol% to 80 mol%, more preferably 10 mol% to 60 mol%, more preferably 15 mol% to 50 mol%, and even more preferably 20 mol% to 45 mol%. By keeping the content of ethylene-derived structural units in the ethylene-vinyl alcohol copolymer within the above range, the balance of mechanical strength, gas barrier properties, and flexibility of the barrier resin layer 102 can be further improved.

[0070] The density of the ethylene-vinyl alcohol copolymer, measured in accordance with JIS K 7112:1999, is preferably 1.05 g / cm³. 3 More than 1.50g / cm 3More preferably, 1.10 g / cm³ 3 More than 1.40g / cm 3 More preferably, 1.13 g / cm³ 3 More than 1.35g / cm 3 More preferably, 1.15 g / cm³ 3 More than 1.30g / cm 3 The following applies: By keeping the density of the ethylene-vinyl alcohol copolymer within the above range, the balance of mechanical strength, gas barrier properties, and flexibility of the barrier resin layer 102 can be further improved.

[0071] In accordance with JIS K 7210:1999, the melt mass flow rate (MFR) of the ethylene-vinyl alcohol copolymer, measured under conditions of 210°C and a 2160g load, is preferably 0.1g / 10 min to 100g / 10 min, more preferably 0.5g / 10 min to 50g / 10 min, even more preferably 1.0g / 10 min to 30g / 10 min, even more preferably 2.0g / 10 min to 20g / 10 min, and even more preferably 3.0g / 10 min to 10g / 10 min, from the viewpoint of further improving the balance of performance in terms of fluidity, film-forming ability, and thermal dimensional stability.

[0072] The melting point of the ethylene-vinyl alcohol copolymer, as measured by differential scanning calorimeter (DSC), is preferably 150°C to 210°C, more preferably 160°C to 200°C, and even more preferably 170°C to 190°C, from the viewpoint of further improving the balance of performance such as film-forming ability, thermal dimensional stability, heat resistance, water vapor barrier properties, oxygen barrier properties, mechanical properties, rigidity, bag-making ability, and fluidity.

[0073] (Polyvinyl alcohol-based resin) Polyvinyl alcohol-based resins are polymers obtained by saponifying polyvinyl acetate polymers, which have hydroxyl groups in their molecules and are preferably water-soluble. The raw material, polyvinyl acetate polymer, may be a homopolymer of vinyl acetate, or it may be a copolymer of other copolymerizable monomers, such as ethylene, propylene, or α-olefins such as 1-butene, up to 30 mol%. If the copolymerized monomer is 30 mol% or less, the barrier properties can be further improved.

[0074] From the viewpoint of further improving barrier properties, the polyvinyl alcohol-based resin preferably further comprises one or more selected from the group consisting of inorganic layered compounds and organosilicon compounds. Examples of inorganic layered compounds include smectite-type layered clay minerals such as montmorillonite, bentonite, saponite, hectorite, paidelite, stevensite, and nontronite; mica such as vermiculite, halloysite, and tetrasilicic mica; and fluorine compounds thereof. Examples of organosilicon compounds include silicon alkoxide compounds and their hydrolysis products.

[0075] (Polyvinylidene chloride resin) The polyvinylidene chloride resin is not particularly limited as long as it mainly contains vinylidene chloride monomer as a constituent unit, and may be polyvinylidene chloride (PVDC) or a copolymer of vinylidene chloride and a monomer copolymerizable with vinylidene chloride. Polyvinylidene chloride resins can be manufactured using conventionally known methods, but various commercially available products can also be used. Asahi Kasei's Saran Resin series is a preferred commercially available product.

[0076] (Polyamide resin) Polyamide resins are not particularly limited as long as they are resins in which a large number of monomers are linked together by amide bonds. Examples include nylon-6, nylon-66, polyamide-12 polyamide-6-66 copolymer, and polymetaxylene adipamide.

[0077] (Polyester resin) The polyester resin is not particularly limited as long as it is a compound obtained by dehydrating and condensing a polycarboxylic acid (dicarboxylic acid) and a polyalcohol, and examples include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.

[0078] (Polyurethane resin) Polyurethane resins can be obtained, for example, by a polyaddition reaction between a polyol having two or more alcoholic hydroxyl groups in one molecule and a polyisocyanate. The polyol preferably comprises one or more polyols selected from the group consisting of polyether polyols, polycarbonate polyols, and polyester polyols, and more preferably comprises one or more polyols selected from the group consisting of polycarbonate polyols and polyester polyols. In other words, the polyurethane resin preferably comprises one or more polyurethane resins selected from the group consisting of polyether-type polyurethane resins, polycarbonate-type polyurethane resins, and polyester-type polyurethane resins, and more preferably comprises one or more polyurethane resins selected from the group consisting of polycarbonate-type polyurethane resins and polyester-type polyurethane resins.

[0079] (Polycarboxylic acid-based resin) Polycarboxylic acid resins have two or more carboxyl groups in their molecule, and examples include polymers or copolymers thereof of α,β-unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, and 3-hexenodioic acid. Alternatively, they may be copolymers of the above α,β-unsaturated carboxylic acids with esters such as ethyl esters, olefins such as ethylene, etc. From the viewpoint of further improving barrier properties, the polycarboxylic acid resin preferably comprises one or more selected from the group consisting of polymers of acrylic acid, polymers of methacrylic acid, polymers of itaconic acid, polymers of fumaric acid, polymers of crotonic acid, polymers of cinnamic acid, and copolymers thereof. More preferably, it comprises one or more selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid. Even more preferably, it comprises at least one selected from polyacrylic acid and polymethacrylic acid.

[0080] (A mixture containing polycarboxylic acid resin, polyamine resin, and polyvalent metal compound) A mixture containing a polycarboxylic acid resin, a polyamine resin, and a polyvalent metal compound contains a polycarboxylic acid resin, a polyamine resin, and a polyvalent metal compound. Polycarboxylic acid resins are as described above.

[0081] Polyamine resins are compounds having two or more amino groups in their main chain, side chains, or terminals, and are preferably polymers. Examples include aliphatic polyamines such as polyallylamine, polyvinylamine, polyethyleneimine, and poly(trimethyleneimine); and polyamides having amino groups in their side chains, such as polylysine and polyarginine. Polyamines in which some of the amino groups have been modified may also be used. From the viewpoint of further improving barrier properties, the polyamine resin preferably contains one or more selected from the group consisting of polyallylamine, polyvinylamine, polyethyleneimine, and poly(trimethyleneimine), and more preferably contains polyethyleneimine.

[0082] Polyvalent metal compounds are, for example, metals and metal compounds belonging to groups 2 through 13 of the periodic table. The polyvalent metal compound preferably comprises one or more selected from the group consisting of divalent or higher metals such as magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), and aluminum (Al), and oxides, hydroxides, halides, carbonates, phosphates, phosphites, hypophosphites, sulfates, and sulfites of these metals; more preferably comprises one or more selected from the group consisting of magnesium oxide, calcium oxide, barium oxide, zinc oxide, magnesium hydroxide, calcium hydroxide, barium hydroxide, and zinc hydroxide; even more preferably comprises one or more selected from the group consisting of zinc oxide and zinc hydroxide; and even more preferably comprises zinc oxide. ru.

[0083] [Layer containing adhesive resin] The adhesive resin preferably comprises one or more selected from the group consisting of ethylene copolymers, acid-modified ethylene polymers, urethane resins, epoxy resins, and vinyl resins, and more preferably comprises an acid-modified ethylene polymer. By including an acid-modified ethylene polymer in the adhesive resin, the adhesion between the polyethylene layer 101 and the barrier resin layer 102 can be further improved, and the recyclability of the barrier film 100 can be further enhanced.

[0084] The density of the acid-modified ethylene polymer, measured in accordance with JIS K 7112:1999, is preferably 0.910 g / cm³. 3 More than 0.970g / cm 3 More preferably, 0.910 g / cm³ 3 More than 0.960g / cm 3 More preferably, 0.915 g / cm³ 3 More than 0.950g / cm 3 More preferably, 0.915 g / cm³ 3 More than 0.940g / cm 3 The following applies: By keeping the density of the acid-modified ethylene polymer within the above range, the balance between the mechanical strength and flexibility of layer 103 containing the adhesive resin can be further improved.

[0085] In accordance with JIS K 7210:1999, the melt mass flow rate (MFR) of acid-modified ethylene polymers, measured under conditions of 190°C and a 2160g load, is preferably 0.1g / 10 min to 100g / 10 min, more preferably 0.5g / 10 min to 50g / 10 min, even more preferably 1.0g / 10 min to 10g / 10 min, and even more preferably 1.1g / 10 min to 5g / 10 min, from the viewpoint of further improving the balance of performance in terms of fluidity, film-forming ability, and thermal dimensional stability.

[0086] The melting point of acid-modified ethylene polymers, as measured by differential scanning calorimeter (DSC), is preferably 100°C to 180°C, more preferably 110°C to 150°C, and even more preferably 120°C to 130°C, from the viewpoint of further improving the balance of performance such as film-forming ability, thermal dimensional stability, heat resistance, water vapor barrier properties, oxygen barrier properties, mechanical properties, rigidity, bag-making ability, and fluidity.

[0087] The content of adhesive resin in the layer 103 containing adhesive resin is preferably 10% by mass or more and 100% by mass or less, more preferably 20% by mass or more and 100% by mass or less, even more preferably 25% by mass or more and 100% by mass or less, even more preferably 50% by mass or more and 100% by mass or less, even more preferably 70% by mass or more and 100% by mass or less, even more preferably 90% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less, when the entire layer 103 containing adhesive resin is considered to be 100% by mass. By setting the content of adhesive resin in the layer 103 containing adhesive resin to be above the above lower limit, the balance of various properties such as thermal dimensional stability, film-forming properties, heat resistance, mechanical properties, and rigidity of the layer 103 containing adhesive resin can be further improved. Furthermore, when the entirety of the adhesive resin-containing layer 103 is considered to be 100% by mass, by keeping the content of the adhesive resin in the adhesive resin-containing layer 103 below the above upper limit, the balance between the processability and continuous productivity of the adhesive resin-containing layer 103 can be further improved.

[0088] <Method for manufacturing barrier film> The barrier film 100 of this embodiment is preferably one selected from the group consisting of unoriented film, uniaxially oriented film, and biaxially oriented film, more preferably a uniaxially oriented film or a biaxially oriented film, and even more preferably a biaxially oriented film. This makes it possible to further improve the balance of performance such as heat resistance, thermal dimensional stability, mechanical properties, water vapor barrier properties, oxygen barrier properties, and tear resistance. Furthermore, from the viewpoint of further improving productivity, the barrier film 100 of this embodiment is preferably a co-extruded film, and it is preferable that at least the polyethylene layer 101 and the barrier resin layer 102 are co-extruded. The barrier film 100 can be obtained, for example, by co-extruding a film into which an ethylene copolymer for forming a polyethylene layer 101, a barrier resin for forming a barrier resin layer 102, and an ethylene copolymer for forming the polyethylene layer 101 are arranged in this order, and then stretching the resulting film using a known stretched film manufacturing method such as uniaxial stretching, simultaneous biaxial stretching, or sequential biaxial stretching. When biaxial stretching is performed, simultaneous biaxial stretching is preferred. The molding apparatus and molding conditions are not particularly limited, and conventionally known molding apparatus and molding conditions can be used. Examples of molding apparatus include T-die extruders, multi-layer T-die extruders, inflation molding machines, or multi-layer inflation molding machines. The conditions for uniaxial stretching and biaxial stretching can, for example, be those of a known barrier film 100. In uniaxial stretching, it is preferable to set the stretching temperature in the MD direction to 100°C to 145°C and the stretching ratio in the MD direction to 4.5 to 6.0 times. In simultaneous biaxial stretching, it is preferable to set the stretching temperature in the MD direction to 100°C to 145°C, the stretching ratio in the MD direction to 3.0 to 7.0 times, and more preferably to 3.0 to 6.0 times. Furthermore, it is preferable to set the stretching temperature in the TD direction to 110°C to 160°C and the stretching ratio in the TD direction to 3.0 to 10.0, more preferably to 3.0 to 8.0, and even more preferably to 3.0 to 6.0. In this embodiment, the barrier film 100 is formed by using a simultaneous biaxial stretching method and stretching the polyethylene copolymer resin contained in the polyethylene layer and the barrier resin in the barrier resin layer at a moderately high temperature, even if the ethylene polymer in the polyethylene layer 101 contains high-density polyethylene.

[0089] <Applications of barrier films / Packaging materials / Packaging products> The barrier film 100 of this embodiment can be suitably used as a packaging film. Furthermore, the barrier film 100 of this embodiment can be suitably used as a packaging material. That is, the packaging material of this embodiment includes the barrier film 100. When used as packaging material, the barrier film 100 of this embodiment may be used alone, or other layers may be laminated to at least one side of the barrier film 100 to form the packaging material. Preferably, the other layers further include one or more selected from the group consisting of an inorganic layer, a base layer, a coating layer, an adhesive layer, and a heat-sealable layer, more preferably one or more selected from the group consisting of an inorganic layer and a coating layer, and even more preferably a coating layer. From the viewpoint of ease of recycling, when these layers are laminated, it is preferable that they be formed from a polyethylene-based resin. Furthermore, the packaging material of this embodiment can be suitably used in packaging bodies. The packaging body is, for example, used for the purpose of packaging an article, and specifically includes the packaging material of this embodiment and the article inside the packaging material. In particular, the packaging body of this embodiment can be suitably used as a food packaging body, and is used for the purpose of packaging food, and specifically includes the packaging material of this embodiment and the food inside the packaging material. The types of food packaged in food packaging are not limited, but examples include baked goods, rice crackers, snack foods, furikake (rice seasoning), and grain powder. Depending on the application, the packaging may consist of only a portion of the packaging material of this embodiment, or substantially the entire packaging may consist of the packaging material of this embodiment.

[0090] From the viewpoint of improving heat sealability, the packaging material of this embodiment preferably further comprises a heat-sealable layer on at least one of its outermost surfaces. As the heat-sealable layer mentioned above, any known heat-sealable layer can be used. The heat-sealable layer includes, for example, one or more layers selected from the group consisting of a resin composition containing one or more polyolefins selected from the group consisting of ethylene, propylene, butene-1, hexene-1, 4-methylpentene-1, octene-1, etc., low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), polypropylene, polypropylene random copolymer, low-crystalline or amorphous ethylene-propylene random copolymer, ethylene-butene-1 random copolymer, propylene-butene-1 random copolymer, etc., a layer formed from a resin composition containing ethylene-vinyl acetate copolymer (EVA), and a layer formed from a resin composition containing EVA and polyolefin. Among these, the heat-sealable layer preferably includes a layer formed from a resin composition containing polyolefin, and more preferably includes a layer formed from a resin composition containing one or more types of polyethylene selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE). As a result, the packaging material is composed of almost a single material (monomaterial), which reduces the work required to separate the materials constituting the packaging material and further improves the recyclability of the packaging material. The thickness of the heat-sealed layer is, for example, 10 μm to 300 μm, preferably 30 μm to 200 μm, and more preferably 50 μm to 150 μm.

[0091] From the viewpoint of further improving recyclability, the content of the ethylene polymer in the packaging material of this embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more, when the total amount of the packaging material is considered as 100% by mass. The higher the ethylene polymer content in the packaging material, the better. Therefore, there is no particular upper limit, but for example, it may be 100% by mass or less, 99.9% by mass or less, or 99.5% by mass or less. Furthermore, from the viewpoint of further improving recyclability, the polyethylene content in the packaging material may be 50% to 100% by mass, 60% to 100% by mass, 70% to 99.9% by mass, 80% to 99.9% by mass, 90% to 99.5% by mass, or 95% to 99.5% by mass, when the total amount of packaging material is considered as 100% by mass. As a result, the packaging material is composed almost entirely of a single material (monomaterial), reducing the need to separate the materials that make up the packaging material and further improving the recyclability of the packaging material.

[0092] The method for manufacturing the package from the barrier film 100 and packaging material is not particularly limited. Methods known in the field of packaging materials / packaging, such as heat sealing and heat cutting, can be used as appropriate.

[0093] The barrier film 100 of this embodiment is preferably used in packaging where good barrier properties are required. The form of the packaging can be, for example, a gusseted bag or a standing pouch (pouch packaging).

[0094] Furthermore, when a package (such as a food packaging bag) is constructed using the barrier film 100 or packaging material of this embodiment, it is preferable that the corona-treated surface is on the inner surface side and the uncorona-treated surface is on the outer surface side. Furthermore, as mentioned above, when additional layers are laminated onto the barrier film 100, it is preferable to laminate them on the corona-treated side. In other words, when a laminate using the barrier film 100 of this embodiment is used in packaging (such as a food packaging bag), it is preferable that the barrier film 100 side of this embodiment becomes the outermost layer of the packaging.

[0095] Although embodiments of the present invention have been described above, these are merely examples, and various other configurations can be adopted. Furthermore, the present invention is not limited to the embodiments described above, and modifications, improvements, etc., within the scope that can achieve the objectives of the present invention are included in the present invention. [Examples]

[0096] <Raw materials> The raw materials used in the examples and comparative examples are shown below. Density was measured in accordance with JIS K 7112:1999. MFR was measured for high-density polyethylene, linear low-density polyethylene, and acid-modified polyethylene in accordance with JIS K 7210:1999, under conditions of 190°C and 2160g load. For ethylene-vinyl alcohol copolymer, it was measured under conditions of 210°C and 2160g load, in accordance with JIS K 7210:1999. Melting point was measured using differential scanning calorimeter (DSC).

[0097] • High-density polyethylene (HDPE1): Density: 0.955 g / cm³ 3 MFR: 0.36g / 10min, Melting point: 130℃ • Linear low-density polyethylene (LLDPE1): Density: 0.928 g / cm³ 3 MFR: 1.9g / 10min, Melting point: 126℃ • Ethylene-vinyl alcohol copolymer (EVOH): Density: 1.210 g / cm³ 3 MFR: 3.8g / 10min, Melting point: 188℃, Ethylene content: 29 mol% • Acid-modified polyethylene (acid-modified PE1): Density: 0.930 g / cm³ 3 MFR: 1.5g / 10min, Melting point: 128℃ • Acid-modified polyethylene (acid-modified PE2): Density: 0.920 g / cm³ 3 MFR: 1.2g / 10min, Melting point: 123℃

[0098] <Manufacturing of barrier films> [Examples, Comparative Examples] For the examples and comparative examples, co-extrusion was performed by T-die extrusion molding to obtain cast sheets with the layer formulations and layer configurations shown in Tables 1 and 2. After obtaining the barrier films for each example, the cast sheets were left unstretched, or subjected to uniaxial stretching or biaxial stretching according to the instructions in Tables 1 and 2. The thickness of each layer is shown in Tables 1 and 2. Note that for the formulations listed in Tables 1 and 2, the content (mass%) of each material within each layer is indicated in parentheses. For example, "Polyethylene layer 1 or adhesive resin layer 1" in Example 7 indicates that it contains 30% by mass of acid-modified polyethylene 1 and 70% by mass of high-density polyethylene 1. The extrusion and stretching conditions are shown below. Multilayer extrusion molding machine: 40mmφ multilayer T-die extrusion molding machine (L / D=32, Sumitomo Heavy Industries Modern Co., Ltd.) Extrusion setting temperature: 230℃ Extrusion molding speed [m / min]: Shown in Tables 1 and 2. Stretching temperature in the MD direction [°C]: Shown in Tables 1 and 2. The stretch ratio in the MD direction [times] is shown in Tables 1 and 2. The stretching temperature in the TD direction [°C] is shown in Tables 1 and 2. The stretch ratio in the TD direction [times] is shown in Tables 1 and 2.

[0099] <Differential Scanning Calorimetry (DSC)> Differential scanning calorimetry (DSC) was performed on each example of barrier film as follows. For each example of barrier film, a differential scanning calorimeter (product name: DiscoveryDSC250, manufactured by TA Instruments Corporation) was used to perform the following differential scanning calorimeter measurements in a nitrogen atmosphere: the first measurement consisted of a heating process from -50°C to 200°C at a heating rate of 10°C / min (1st Run); the second measurement consisted of an isothermal process of holding at 200°C for 5 minutes, a cooling process from 200°C to -50°C at a cooling rate of 10°C / min (cooling measurement), a holding process at -50°C for 5 minutes, and a heating process from -50°C to 200°C at a heating rate of 10°C / min (2nd Run). In the DSC curve 2 (2nd Run) obtained from the second differential scanning calorimetry, we checked whether endothermic peaks were observed in the ranges of 100°C to 140°C and 150°C to 190°C. Furthermore, in the DSC curve 1 (1st Run) obtained from the first differential scanning calorimetry, the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C, which is ΔH. 1st (J / g) is used, and the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C in the DSC curve 2 (2ndRun) obtained by the second differential scanning calorimetry, and is then given as ΔH. 2nd (J / g) The obtained ΔH 1st (J / g) and ΔH 2nd From (J / g), (ΔH 1st -ΔH 2nd The (J / g) ratio was calculated. Furthermore, in the DSC curve 1 (1st Run) obtained from the first differential scanning calorimetry, the heat of fusion is calculated from the endothermic peak observed in the range of 150°C to 190°C, which is ΔH. 1st(150-190) (J / g) is used, and the heat of fusion is calculated from the endothermic peak observed in the range of 150°C to 190°C in the DSC curve 2 (2ndRun) obtained by the second differential scanning calorimetry, and is then given as ΔH. 2nd(150-190) (J / g) The obtained ΔH 1st(150-190) (J / g) and ΔH 2nd(150-190) From (J / g), (ΔH 1st(150-190) -ΔH 2nd(150-190) The (J / g) ratio was calculated. The heat of fusion for each endothermic peak was calculated by determining the area enclosed by the endothermic fusion curve containing each endothermic peak and the baseline. The baseline was defined as the line connecting the point where the change in Deriv. Heat Flow begins (i.e., where the flat region of Deriv. Heat Flow ends) and the point where the change in Deriv. Heat Flow ends (i.e., where Deriv. Heat Flow enters the flat region), obtained by differentiating the Heat Flow with respect to time before and after the endothermic peak. Furthermore, if multiple endothermic peaks were observed within each temperature range, the largest peak was considered the endothermic peak.

[0100] <Tensile modulus> A 15 mm x 15 cm test specimen was cut from each example of barrier film. Then, using a tensile testing machine manufactured by Orientec, the tensile modulus T1 in the MD direction and the tensile modulus T2 in the TD direction of the test specimen were measured in accordance with JIS K7127:1999, under the conditions of a measurement temperature of 23 ± 2 °C, 50 ± 5% RH, and a tensile speed of 5 mm / min. From the obtained values, the sum of T1 and T2 was calculated.

[0101] <Heat shrinkage coefficient at 120°C> The thermal shrinkage rate of the barrier film at 120°C was measured in accordance with JIS C2151:2019. A 10.00 cm × 10.00 cm test specimen was cut from each example of barrier film. Next, the test specimen was suspended without force in a hot air circulating constant temperature bath (ADVANTEC, product name: DRM620DE). Then, the test specimen was heat-treated at 120°C for 15 minutes. After the test specimen cooled to room temperature, its length was measured. The length of the heat-treated test specimen in the MD direction was measured as follows: 120 Let the measurement be in [cm], and the thermal shrinkage rate in the MD direction [%] be 100 × (10.00 - MD 120 The length of the test specimen in the TD direction after heat treatment was calculated using ) / 10.00. 120 Let the measurement be in [cm], and the thermal shrinkage rate in the TD direction [%] be 100 × (10.00 - TD 120The calculation was performed using ) / 10.00. The above measurement was performed three times, and the average of the obtained values ​​was adopted as the thermal shrinkage rate of the barrier film at 120°C in the MD direction and TD direction, respectively.

[0102] <Water vapor transmission rate> The water vapor transmission rate of barrier films was measured according to the following method in accordance with JIS Z 0208:1976. Each example of the barrier film is folded in half, and both sides are heat-sealed to create an inner surface area of ​​0.01 m². 2 A bag was constructed to achieve the following result. 10g of calcium chloride was placed inside the bag, the opening was heat-sealed, and the bag was then stored for 72 hours at 40°C and 90% RH. The weight of calcium chloride was measured before and after storage, and the water vapor transmission rate (g / m³) was calculated from the difference. 2 The number of days was calculated. From the obtained water vapor transmission rate and the thickness of the barrier film used for measurement, the water vapor transmission rate was calculated when the barrier film thickness was converted to 20 μm.

[0103] <Oxygen permeability> Oxygen permeability of barrier films in each example (mL / (m²) 2 The pressure (·day·MPa) was measured under conditions of 20°C and 80%RH in accordance with JIS K7126:2006. From the obtained oxygen permeability and the thickness of the barrier resin layer of the barrier film used for measurement, the oxygen permeability when the thickness of the barrier resin layer is converted to 3 μm was calculated using the following formula (1). Equation (1): Oxygen permeability B [mL / (m²)] converted to a thickness of 3 μm 2 (Day·MPa) = (Barrier resin layer thickness a [μm] / 3 [μm]) × Oxygen permeability measurement value A [mL / (m 2 (·day·MPa)

[0104] <Tear strength> From each example of barrier film, test specimens measuring 63.5 mm in the MD direction and 50.0 mm in the TD direction were cut. For each of these test specimens, the tear strength (mN) in the MD direction was measured using a light-load tear tester (Toyo Seiki Seisakusho Co., Ltd., Model-D) under the conditions of a tear length of 12.7 mm and a pendulum lift angle of 90°, by appropriately combining pendulum weights from 16 g to 720 g according to the measurement load range. Furthermore, test specimens measuring 63.5 mm in the MD direction and 50.0 mm in the TD direction were cut from each example of barrier film. For each of the above test specimens, the tear strength (mN) in the TD direction was measured using a light-load tear tester (Toyo Seiki Seisakusho Co., Ltd., Model-D) under the conditions of a tear length of 12.7 mm and a pendulum lift angle of 90°, by appropriately combining pendulum weights from 16 g to 720 g according to the measurement load range.

[0105] <Peel strength> Using barrier films cut to a width of 15 mm for each example, the peel strength (N / 15 mm) between the polyethylene layer and the barrier resin layer was measured under the conditions of 23 ± 2°C, peel angle of 90°, peel speed of 300 mm / min, and tensile strength in the MD direction.

[0106] <Heat fusion evaluation> Two polyethylene layers of barrier film, cut to a width of 15 mm for each example, were bonded together, sandwiched between 12 μm thick biaxially oriented polyethylene terephthalate films, and then heat-sealed at temperatures of 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C at a pressure of 2.0 kgf / cm² using a heat seal tester (Tester Industries Co., Ltd., TP-701-B). 2 After obtaining laminated films by heat-sealing them with a sealing time of 1.0 second, the two barrier films within the laminated film were peeled off under the conditions of 90° peeling, peeling speed of 300 mm / min, and tensile strength in the MD direction. The peel strength at that time was defined as the heat-sealing strength (N / 15 mm).

[0107] <Bag-making properties (presence or absence of wrinkles during heat sealing)> Two polyethylene layers of barrier film, cut to a width of 15 mm for each example, were bonded together, sandwiched between 12 μm thick biaxially oriented polyethylene terephthalate films, and then heat-sealed at temperatures of 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C at a pressure of 2.0 kgf / cm² using a heat seal tester (Tester Industries Co., Ltd., TP-701-B). 2 Laminated films were obtained by heat-sealing them under the condition of a sealing time of 1.0 second. Next, the presence or absence of heat wrinkles in the sealed portion of the laminated films obtained by heat-sealing at each temperature was visually observed and evaluated according to the following criteria: Laminated films obtained at a heat-sealing temperature of 120°C or lower were evaluated as "Excellent" if all evaluations were A, laminated films obtained at a heat-sealing temperature of 120°C or lower were evaluated as "Pass" if there was one or more evaluations of B and no evaluations of C, and laminated films obtained at a heat-sealing temperature of 120°C or lower were evaluated as "Fail" if there was even one evaluation of C. (Evaluation Criteria) A (Good): No wrinkles were observed in the seal. B (Slightly Poor): Distortion was observed in the seal area. C (Defective): Wrinkles were observed in the seal.

[0108] [Table 1]

[0109] [Table 2] [Explanation of Symbols]

[0110] 100 Barrier film 101 Polyethylene layer 102 Barrier resin layer 103 Layer containing adhesive resin

Claims

1. It comprises a polyethylene layer and a barrier resin layer, The polyethylene layer contains an ethylene polymer. The barrier resin layer comprises a barrier resin. Using a differential scanning calorimeter (DSC), the process consists of a first differential scanning calorimetry measurement (1st Run) where the temperature is raised from -50°C to 200°C at a heating rate of 10°C / min, an isothermal process where the temperature is maintained at 200°C for 5 minutes, and a cooling process (cooling measurement) where the temperature is cooled from 200°C to -50°C at a cooling rate of 10°C / min. The process involves holding the temperature at -50°C for 5 minutes, The second differential scanning calorimetry consists of a process (2nd Run) in which the temperature is raised from -50°C to 200°C at a heating rate of 10°C / min, When you continue doing that, In the DSC curve 2 (2nd Run) obtained from the second differential scanning calorimetry, at least one endothermic peak was observed in each of the ranges of 100°C to 140°C and 150°C to 190°C. In the DSC curve 1 (1st Run) obtained by the first differential scanning calorimetry, the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C, which is ΔH. 1st (J / g) In the DSC curve 2 (2nd Run) obtained by the second differential scanning calorimetry, the heat of fusion is calculated from the endothermic peak observed in the range of 0°C to 140°C, which is ΔH. 2nd When (J / g), ΔH 1st -ΔH 2nd However, it is a barrier film with a saturation level of 1.0 J / g or more and 50.0 J / g or less.

2. The aforementioned ΔH 2nd The barrier film according to claim 1, wherein the concentration is 205.0 J / g or less.

3. The aforementioned ΔH 1st The barrier film according to claim 1 or 2, wherein the concentration is 210.0 J / g or less.

4. A barrier film according to any one of claims 1 to 3, having a layer containing an adhesive resin.

5. The density of the ethylene polymer in the polyethylene layer or the layer containing the adhesive resin, as measured in accordance with JIS K 7112:1999, is 0.910 g / cm³. 3 0.970g / cm or more 3 The barrier film according to any one of claims 1 to 4, which is as follows:

6. A barrier film according to any one of claims 1 to 5, wherein the tensile modulus in the MD direction is 600 MPa or more and 3300 MPa or less, as measured using a tensile testing machine in accordance with JIS K7127:1999 under the conditions of a measurement temperature of 23±2°C, 50±5%RH, and a tensile speed of 5 mm / min.

7. A barrier film according to any one of claims 1 to 6, wherein the thermal shrinkage rate in the MD direction after heat treatment at 120°C for 15 minutes, as measured in accordance with JIS C2151:2019, is 28.0% or less.

8. Measured by the following method 1 in accordance with JIS Z 0208:1976, and the water vapor transmission rate when the thickness of the barrier film is converted to 20 μm is 20.0 g / (m 2 ·day) or less, the barrier film according to any one of claims 1 to 7. (Method 1) The barrier film is folded in half, and two sides are heat-sealed to create an inner surface area of ​​0.01 m². 2 A bag is prepared so that 10 g of calcium chloride is placed inside the bag, the opening of the bag is heat-sealed, and the bag is then stored for 72 hours in an environment of 40°C and 90% RH. The weight of the calcium chloride is measured before and after storage, and the water vapor transmission rate (g / m) is calculated from the difference. 2 Calculate the day.

9. In accordance with JIS K7126:2006, measured under conditions of 20°C and 80% RH, the oxygen permeability when the thickness of the barrier resin layer is converted to 3 μm is 30.0 mL / (m²). 2 A barrier film according to any one of claims 1 to 8, wherein the density is less than or equal to (day MPa).

10. The polyethylene layer contains polyethylene as the ethylene polymer, The barrier film according to any one of claims 1 to 9, wherein when the entire polyethylene layer is considered to be 100% by mass, the polyethylene content in the polyethylene layer is 50% by mass or more.

11. The barrier film according to any one of claims 1 to 10, wherein the barrier resin comprises one or more selected from the group consisting of ethylene-vinyl alcohol copolymer, polyvinyl alcohol-based resin, polyvinylidene chloride-based resin, polyamide-based resin, polyester-based resin, polyurethane-based resin, polycarboxylic acid-based resin, and a mixture containing a polycarboxylic acid-based resin, a polyamine-based resin, and a polyvalent metal compound.

12. The barrier film according to any one of claims 1 to 11, wherein when the entirety of the barrier resin layer is considered to be 100% by mass, the content of the barrier resin in the barrier resin layer is 50% by mass or more.

13. A barrier film according to any one of claims 1 to 12, which is a co-extruded film.

14. A barrier film according to any one of claims 1 to 13, which is one selected from the group consisting of an unoriented film, a uniaxially oriented film, and a biaxially oriented film.

15. The barrier film according to any one of claims 1 to 14, wherein the barrier resin layer is not the outermost layer.

16. The barrier film according to claim 4, wherein the adhesive resin comprises one or more selected from the group consisting of ethylene copolymers, acid-modified ethylene polymers, urethane resins, epoxy resins, and vinyl resins.

17. The barrier film according to any one of claims 1 to 16, wherein the barrier film has one laminated structure selected from the group consisting of polyethylene layer / barrier resin layer / polyethylene layer and polyethylene layer / adhesive resin layer / barrier resin layer / adhesive resin layer / polyethylene layer.

18. A barrier film according to any one of claims 1 to 17, wherein the tear strength of the barrier film in the MD direction is 15 mN or more and 3000 mN or less, as measured using a light-load tear tester under the following conditions: specimen size: MD direction: 63.5 mm, TD direction: 50.0 mm, tear length: 12.7 mm, and pendulum lift angle: 90°.

19. A barrier film according to any one of claims 1 to 18, wherein when the following method 2 is performed, it cannot be peeled off, or the peel strength measured by the following method 2 is 0.2 N / 15 mm or more. (Method 2) Using the barrier film cut to a width of 15 mm, the peel strength (N / 15 mm) between the polyethylene layer and the barrier resin layer is measured under the conditions of 23 ± 2°C, peel angle of 90°, peel speed of 300 mm / min, and tensile strength in the MD direction.

20. A barrier film according to any one of claims 1 to 19, wherein the heat-sealing temperature at which the heat-sealing strength measured by method 3 below is 130°C or higher is 1.0 N / 15 mm or higher. (Method 3) Two 15 mm wide strips of the barrier film are bonded together, then sandwiched between two 12 μm thick biaxially oriented polyethylene terephthalate films. Finally, a heat seal tester is used to measure the temperature at 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C, and the pressure at 2.0 kgf / cm². 2 A laminated film is prepared by heat fusion under the condition of a sealing time of 1.0 second. Then, the two barrier films in the laminated film are peeled off under the conditions of 90° peeling, peeling speed of 300 mm / min, and tensile in the MD direction, and the peel strength at that time is defined as the heat fusion strength (N / 15 mm).

21. The barrier film according to any one of claims 1 to 20, wherein the thickness of the barrier resin layer is 0.5 μm or more and 20.0 μm or less.

22. The barrier film according to any one of claims 1 to 21, wherein the thickness of one polyethylene layer is 2.0 μm or more and 100.0 μm or less.

23. The barrier film according to any one of claims 1 to 22, wherein the ratio of the thickness of the barrier resin layer to the total thickness of the barrier film is 1% or more and 30% or less.

24. The barrier film according to any one of claims 1 to 23, wherein the content of the ethylene polymer in the barrier film is 50% by mass or more and 100% by mass or less when the total mass of the barrier film is considered to be 100% by mass.

25. A barrier film according to any one of claims 1 to 24, which is a packaging film.

26. A packaging material comprising a barrier film according to any one of claims 1 to 25.

27. The packaging material according to claim 26, A package containing the article contained within the aforementioned packaging material.

Citation Information

Patent Citations

  • Polyethylene laminate for packaging material and packaging material made of said laminate

    JP2022079510A

  • Stretched polyethylene film

    JP2023031061A